Kebijakan Kerja Hybrid, Job Autonomy, dan Pos terhadap Turnover Intention melalui Employee Engagement pada PT Quinsis Lintas Mitra - Syaeful Yusuf Surawijaya; Rian Sri Rahayu; Kasmad Kasmad (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to analyze the effect of Hybrid Work Policy, Job Autonomy, and Perceived Organizational Support on Turnover Intention through Employee Engagement as an intervening variable among employees of PT Quinsis Lintas Mitra, an IT Services company in Indonesia whose turnover rate escalated from 14% (2022) to 23% (2025). This study used a quantitative approach with an explanatory, cross-sectional design. The sample comprised the entire population of 150 employees determined through saturated sampling. Data were collected using a 1–5 Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The outer model evaluation showed that all indicators were valid (outer loading > 0.70) and reliable (Cronbach's Alpha and Composite Reliability > 0.90). Hypothesis testing revealed that Job Autonomy and Perceived Organizational Support significantly affect Employee Engagement, whereas Hybrid Work Policy does not. Regarding Turnover Intention, Job Autonomy has a significant positive effect, Perceived Organizational Support has a significant negative effect, while Hybrid Work Policy and Employee Engagement show no significant effect. Employee Engagement was also found unable to mediate the relationship between the three independent variables and Turnover Intention. These findings suggest that employee retention strategies in IT Services firms should focus on strengthening Perceived Organizational Support and managing Job Autonomy alongside transparent career paths and competitive compensation.